KONSEP CRYPTOCURRENCY SEBAGAI ALAT PEMBAYARAN UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Febrianto, Andre; Ismail; Iryani, Dewi (LPPM STIH Awang Long, 2025)
The rapid development of cryptocurrency as a global digital financial instrument has posed legal challenges, particularly regarding its status as a medium of exchange. In Indonesia, the legal position of cryptocurrency is characterized by dualism and ambiguity. On one hand, the Commodity Futures Trading Regulatory Agency (BAPPEBTI) regulates and recognizes cryptocurrency as a commodity tradable on futures exchanges. On the other hand, Bank Indonesia (BI) strictly prohibits its use as legal tender, based on Law Number 7 of 2011 concerning Currency, which mandates the Rupiah as the sole legal tender. This research aims to analyze the legal consequences of using cryptocurrency as a payment instrument in Indonesia and to formulate a regulatory concept that can ensure legal certainty. This study employs a normative legal research method with a qualitative approach. The data utilized consists of primary, secondary, and tertiary legal materials. The results indicate that the use of cryptocurrency as a payment instrument results in the civil nullification of agreements (based on Article 1337 of the Indonesian Civil Code), administrative sanctions from BI and BAPPEBTI, and potential criminal liability related to Money Laundering Crimes (TPPU). To achieve legal certainty, an integrated regulatory framework is required, encompassing: (1) clear classification of cryptocurrencies (payment, utility, and security tokens); (2) the establishment of specific legislation regarding digital assets; (3) inter-agency coordination among regulators (BI, OJK, BAPPEBTI, and Kominfo); (4) effective consumer protection and dispute resolution mechanisms; and (5) the integration of Anti-Money Laundering (AML) and Know Your Customer (KYC) principles. Policy recommendations include strengthening public awareness, adopting a regulatory sandbox, and accelerating the Digital Rupiah Central Bank Digital Currency (CBDC) project.